Both Maturation and Survival of Human Dendritic Cells are Impaired in the Presence of Anergic/Suppressor T Cells - L. Frasca; C. Scottà; G. Lombardi; E. Piccolella (Clinical and Developmental Immunology)
T cell suppression is a well established phenomenon, but the mechanisms involved are still a matter of debate. Mouse anergic T cells were shown to suppress responder T cell activation by inhibiting the antigen presenting function of DC. In the present work we studied the effects of co-culturing human anergic CD4+ T cells with autologous dendritic cells (DC) at different stages of maturation. Either DC maturation or survival, depending on whether immature or mature DC where used as APC, was impaired in the presence of anergic cells. Indeed, MHC and costimulatory molecule up-regulation was inhibited in immature DC, whereas apoptotic phenomena were favored in mature DC and consequently in responder T cells. Defective ligation of CD40 by CD40L (CD154) was responsible for CD95-mediated and spontaneous apoptosis of DC as well as for a failure of their maturation process. These findings indicate that lack of activation of CD40 on DC by CD40L-defective anergic cells might be the primary event involved in T cell suppression and support the role of CD40 signaling in regulating both activation and survival of DC.